Generalized hybrid coronary revascularization vs. conventional off-pump coronary artery bypass grafting for multivessel coronary artery disease - Zhang, Shuai; Li, Ping; Li, Guang; Yan, Yunfeng; Sun, Tao; Lin, Ji; Zhang, Chenhao; Liu, Shuo; Qu, Zheng; You, Bin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHybrid coronary revascularization (HCR) has been demonstrated as a safe and effective revascularization strategy in selected patients with multivessel coronary artery disease; however, the inclusion criteria are too strict.ObjectivesThis study was conducted to compare in-hospital and midterm outcomes after generalized HCR and off-pump coronary artery bypass (OPCABG) in patients with multivessel coronary artery disease.MethodsWe proposed a generalized idea of HCR. First, the PCI for non-LAD vessels suitable for coronary stents was performed. Then, MICS-CABG for LIMA to the LAD and saphenous to other non-LAD vessels that were not suitable for stents or stenting failed. Propensity score matching was used, and 222 patients (n = 111 in both the generalized HCR and OPCABG groups) were enrolled in the study. The primary endpoint was a major adverse cardiac or cerebrovascular event (MACCE) over midterm follow-up, and the secondary endpoints were in-hospital outcomes.ResultsNo signiﬁcant difference was observed in the cumulative rate of MACCE (9.9% vs. 16.2%; HR, 0.567; 95% CL, 0.268–1.201; P = 0.138) between the generalized HCR and OPCABG groups. The residual SYNTAX score was similar between two groups (6.3 ± 5.5 for generalized HCR vs. 6.8 ± 5.3 for OPCABG; P = 0.486). Compared with OPCABG, generalized HCR was associated with a signiﬁcantly lower intra-aortic balloon pump (IABP) implantation rate (2.7% vs. 9.9%; P = 0.027) and shorter postoperative length of stay (6.3 ± 3.2 vs. 7.7 ± 3.0; P = 0.001).ConclusionsThe generalized HCR procedure appears to be safe and efﬁcacious, with outcomes similar to those of standard off-pump CABG and satisfactory completeness of revascularization.